The ship of the disappeared - Pinto de Almeida, Leonardo (Escritura e Imagen, 2021)
This research revolves around three novels that address Peru’s republican period and focus on the episode of fujimorist and senderist violence. These include La barca (E. J. Huarag, 2007), La hora azul (A. Cueto, 2005) and Rosa Cuchillo (O. Colchado, 1997). Far from the scientific pretensions of history, literature focuses on facts in which affections are manifested. In the present case, the question of violence, as discussed in these novels, allows what is absent through the figure of the disappeared to be made present. Is it possible to make a novel of those who are not there? This article attempts to think about the event of disappearance and its relations with both violence and the production of subjectivity. Just as history works with facts to produce a story that explains them, in the case of literature what is pursued is to create an “experience” that promotes spaces of transformation/discomfort.
Keywords: disappearance; violence; literature; history